Fundraising for social change - Klein, Kim; Yogi, Stan (Kim Klein's fundraising series, 2022)
"This will be the 8th edition of one of the bestselling books on effective, mission-driven fundraising that is widely used in the field by nonprofit organizations across the country. It has often been called "the Bible of grassroots fundraising" and is a soup to nuts description of how to build, maintain and expand an individual donor program. There will be updates to many of the existing chapters, but the largest difference in this edition will be new chapters that touch on a number of more current issues. While all previous editions of this book have noted the racism that can be present in donor relations, it is important that racism and white supremacy be addressed more directly in this edition. That is where co-author Stan Yogi comes into play. Stan is an expert in legacy giving, capital campaigns, and fundraising for faith- based organizations, LGBTQ organizations and racial justice organizations. Stan's experience as a Japanese American, his work for redress for Japanese Americans, and his extensive research on social movements gives him important insight into the racial dynamics present in fundraising."--